Advances in point-contact spectroscopy: two-band superconductor MgB2 (Review Article): - Yanson, I.K.; Naidyuk, Yu.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Analysis of the point-contact spectroscopy (PCS) data on the new dramatic high-Tc superconductor magnesium diboride MgB2 reveals quite different behavior of two disconnected s and p electronic bands, deriving from their anisotropy, different dimensionality, and electron—phonon interaction. PCS allows direct registration of both the superconducting gaps and electron—phonon interaction spectral function of the two-dimensional s and three-dimensional p band, establishing correlation between the gap value and intensity of the high-Tc driving force — the E2g boron vibration mode. PCS data on some nonsuperconducting transition-metal diborides are surveyed for comparison.